Fluorouracil, Leucovorin and Irinotecan Combined with Intra-Arterial Hepatic Infusion of Drug-Eluting Beads Preloaded with Irinotecan in Unresectable Colorectal Liver Metastases: Side Effects and Results of a Concomitant Treatment Schedule. Clinical Investigation. Issue 5 (September 2014) - Kekez, Domina; Badzek, Sasa; Prejac, Juraj; Gorsic, Irma; Golem, Hilda; Librenjak, Niksa; Perkov, Drazen; Smiljanic, Ranko; Plestina, Stjepko
Aim: Safety evaluation of concomitant systemic chemotherapy and liver chemoembolization in patients with colorectal cancer. Patients and Methods: Seven patients with metastases confined to the liver were included and stratified into two groups, depending of dosage of systemic chemotherapy. The first group received systemic chemotherapy (FOLFIRI) with 20% dose reduction, and the second group received the full dose of the same chemotherapy. In both groups, chemoembolization of liver metastases with drug-eluting bead irinotecan (DEBIRI) was performed following the application of systemic chemotherapy. The toxicity profiles of the two groups were compared. Results: Of the 7 patients included, 4 received the reduced systemic chemotherapy dose and 3 received the full chemotherapy dose. DEBIRI was performed in all 7 patients. The main toxicities observed in the reduced chemotherapy dose group were leukopenia (25%), anorexia (75%), diarrhea (25%), vomiting (25%), right upper abdominal quadrant pain (100%) and elevated serum amylase level (25%). Main toxicities observed in the full chemotherapy dose group were anorexia (66.6%), vomiting (33.3%), right upper abdominal quadrant pain (100%), and elevated serum amylase level (66.6%). There were no significant differences between the two groups (P = 0.78541). Conclusions: Patients with isolated liver metastases from a colorectal primary can safely be treated with DEBIRI chemoembolization and a full dose of systemic chemotherapy (FOLFIRI).